2019
DOI: 10.1016/j.jor.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Late acetabular dysplasia after successful treatment for developmental dysplasia of the hip using the Pavlik method: A systematic literature review

Abstract: The Pavlik method is the most common method used for treatment of developmental dysplasia of the hip (DDH). Late acetabular dysplasia despite successful treatment, however, has had varied reporting. A systematic review was performed, investigating the long-term outcomes of DDH treated with the Pavlik method. Seventeen studies met inclusionary criteria, including 6029 hips treated with an average of 5.29 years follow-up. Radiographic evidence of late dysplasia was present in 280 hips, with 109 hips requiring ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 28 publications
0
36
2
1
Order By: Relevance
“…The current study aims to evaluate primary acetabular dysplasia, excluding residual acetabular dysplasia secondary to management with surgery or conservative method, and this is the most significant difference from the earlier studies in the literature (15). Our findings show that abduction orthosis is an effective method in the treatment of patients with acetabular dysplasia.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The current study aims to evaluate primary acetabular dysplasia, excluding residual acetabular dysplasia secondary to management with surgery or conservative method, and this is the most significant difference from the earlier studies in the literature (15). Our findings show that abduction orthosis is an effective method in the treatment of patients with acetabular dysplasia.…”
Section: Discussionmentioning
confidence: 85%
“…Acetabular dysplasia could be easily underestimated due to late-onset symptoms or even asymptomatic contrary to hip dislocation, but prevalence and importance are more than predicted. In a systematic review of the literature conducted by Shaw and et al(15), radiographic evidence of late dysplasia was present in 9,49% hips and 4,14% hips requiring additional surgery of 6029 hips treated with the Pavlik method an average of 5.29 years followup. Dornacher et al detected residual dysplasia in 30% of their patients on pelvic X-rays when children started walking even after successful ultrasound-monitored treatment(17).Sarkissian et al showed that 17% of all infants, who had achieved both normal ultrasonographic and clinical examinations at an average of three months, demonstrated radiographic signs of acetabular dysplasia at the age of average six months(18).…”
mentioning
confidence: 99%
“…There is extensive literature discussing the strengths of both US and plain films for the diagnosis of DDH, as well as the incidence of late-presenting dysplasia in various cohorts 11,12,19–21. Barrera et al22 discuss the various imaging techniques that are utilized over the course of treatment for DDH.…”
Section: Discussionmentioning
confidence: 99%
“…Graf type IIc hips are marginally more difficult to treat than less severe diagnoses, understandably requiring longer treatment lengths and more aggressive interventions [18,19]. Better outcomes are often associated with a younger age at treatment initiation while the hip is still undeveloped [10,20,21]. Regardless of severity or Graf type, DDH does not have a treatment protocol that is universally agreed upon in the orthopedic community.…”
Section: Discussionmentioning
confidence: 99%